2023
DOI: 10.3389/fimmu.2023.1129190
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in gut immunological barrier in SARS-CoV-2 infection and their prognostic potential

Abstract: Although coronavirus disease 2019 (COVID-19) is primarily associated with mild respiratory symptoms, a subset of patients may develop more complicated disease with systemic complications and multiple organ injury. The gastrointestinal tract may be directly infected by SARS-CoV-2 or secondarily affected by viremia and the release of inflammatory mediators that cause viral entry from the respiratory epithelium. Impaired intestinal barrier function in SARS-CoV-2 infection is a key factor leading to excessive micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…The intestinal barrier can be maintained and self‐repaired to a certain extent by intestinal flora and metabolites. However, excessive activation of the immune response and immune microenvironment can cause further epithelial damage 106 . A recent Mendelian randomization study on gut microbiota and COVID‐19 susceptibility and severity further suggested a correlation between gut microbiota dysbiosis and COVID‐19 symptoms, with some dysregulated flora, such as Subdoligranulum and Lactobacillale have been found to be associated with the severity of the disease ( p < 0.05).…”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal barrier can be maintained and self‐repaired to a certain extent by intestinal flora and metabolites. However, excessive activation of the immune response and immune microenvironment can cause further epithelial damage 106 . A recent Mendelian randomization study on gut microbiota and COVID‐19 susceptibility and severity further suggested a correlation between gut microbiota dysbiosis and COVID‐19 symptoms, with some dysregulated flora, such as Subdoligranulum and Lactobacillale have been found to be associated with the severity of the disease ( p < 0.05).…”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%
“…However, excessive activation of the immune response and immune microenvironment can cause further epithelial damage. 106 A recent Mendelian randomization study on gut microbiota and COVID‐19 susceptibility and severity further suggested a correlation between gut microbiota dysbiosis and COVID‐19 symptoms, with some dysregulated flora, such as Subdoligranulum and Lactobacillale have been found to be associated with the severity of the disease ( p < 0.05). These findings suggest that the gut microbiota may have a causal relationship with the severity of COVID‐19, thus providing new evidence and ideas for the study of the pathogenesis of SARS‐CoV‐2 mediated by gut microbiota.…”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%
“…In addition to respiratory complications, up to 30% of COVID-19 patients experience gastrointestinal symptoms, including diarrhea, abdominal discomfort, loss of appetite and vomiting (Al-Momani et al, n.d.; Hayashi et al, 2021; Zhong et al, 2020). Some COVID-19 patients even develop severe duodenitis associated with gastrointestinal bleeding requiring red blood cell transfusion (Cappell and Friedel, 2023; Eleftheriotis et al, 2023). Impaired intestinal barrier function in SARS-CoV-2 infection allows microbial and endotoxin translocation, which triggers inflammation and may lead to sepsis or contribute to chronic inflammation (Assimakopoulos et al, 2022; Eleftheriotis et al, 2023; Yamada et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Some COVID-19 patients even develop severe duodenitis associated with gastrointestinal bleeding requiring red blood cell transfusion (Cappell and Friedel, 2023; Eleftheriotis et al, 2023). Impaired intestinal barrier function in SARS-CoV-2 infection allows microbial and endotoxin translocation, which triggers inflammation and may lead to sepsis or contribute to chronic inflammation (Assimakopoulos et al, 2022; Eleftheriotis et al, 2023; Yamada et al, 2022). Altogether, accumulating evidence suggests that SARS-CoV-2 infection of the gastrointestinal tract plays a relevant role in COVID-19 (Jin et al, 2021; Scaldaferri et al, 2020; Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation